Pension Fund Calculations for Regular Retirees Using the Projected Unit Credit Method and the Individual Level Premium Method in the Case Study PT Dynacast Indonesia. - Hukama, Atha; Pangestu, Rizcki; Laksito, Grida Saktian (International Journal of Global Operations Research, 2024)
The pension program provider requires actuarial valuation to estimate the necessary fund amount for pension payments. This research employs the projected unit credit and individual level premium methods. The findings indicate that the valuation of pension benefits, assuming a career average salary, is lower compared to other salary assumptions. Conversely, the final valuation of project unit credit using the individual level premium method is smaller than that of the projected unit credit method, which is more suitable for participants in the pension funding program. A pension fund program represents a form of future planning aimed at ensuring the well-being of employees during retirement. It embodies a company's responsibility towards employees who have dedicated themselves during their working years. Such a program offers a sense of security regarding an employee's financial future post-retirement and fosters peace of mind, knowing that their well-being in old age is assured.